Hubungan Usia dan Riwayat Abortus dengan Kejadian Abortus di Puskesmas Peninggalan Kabupaten Musi Banyuasin Provinsi Sumatera Selatan Tahun 2024 - Friza Novita Sari Situmorang; Wayan Lusiana Wulandari; Yesica Geovany Sianipar; Rismalia Tarigan; Pitri Indriani Purba; Novitaria Zega (Lembaga Pengembangan Kinerja Dosen, 2025)
Abortion is a condition in which the results of conception are expelled before the fetus has the ability to survive outside the womb, usually occurring at a gestational age of less than 20 weeks or with a fetal weight of less than 500 grams. In 2022, K1 coverage reached 100% in several areas such as Lahat Regency, Musi Banyuasin, East OKU, Ogan Ilir, Empat Lawang, and the cities of Palembang, Prabumulih, and Pagar Alam. Meanwhile, the lowest K1 coverage was found in South OKU Regency, with a percentage of 56.6%. The purpose of this study was to identify the age and history of abortion with the incidence of abortion at the Peninggalan Health Center, Musi Banyuasin Regency, South Sumatra Province in 2024. This study used a Case Control design, the research time was April-June 2024, with a population of 117 people. Using a 1:1 comparison of 38 case samples and 38 control samples, so that the sample was 76 people. This study used Chi Square Test analysis. The majority of respondents aged <20 years and >35 years who experienced abortion were 28 people (33.2%). The majority of respondents who had a history of abortion and experienced abortion were 31 people (40.1%). There is a significant relationship between age and history of abortion with the incidence of abortion at the Peninggalan Health Center, Musi Banyuasin Regency, South Sumatra Province, with a p-value <0.05 (0.001).